Strategy For Development of Pharmaceutical Salt Business in Improving The Welfare of The Salt Farmers from Islamic Perspective (ADI Journal on Recent Innovation (AJRI), 2022)
Indonesia is the largest archipelagic country with a manageable sea area of 5.8 million km2. The marine and fisheries sector in Indonesia has become very strategic for the Indonesian people, especially in coastal communities, where most people rely on marine resources as a livelihood in the economic activities of coastal communities. One of the marine resources that can be processed is salt from seawater. The main objective of this research is to formulate a strategy for developing a pharmaceutical salt business to improve the welfare of smallholder salt farmers. The design of this study uses the SWOT-AHP method. The priority is to find strategic priorities that can improve the welfare of farmers, which refers to the economic perspective.